Production of Micro- and Nanofibrillated Cellulose through an Aqueous Counter Collision System Followed by Ultrasound: Effect of Mechanical Pretreatments - Dimitrios Tsalagkas; Lindong Zhai; Abdullahil Kafy; Jung Woong Kim; Hyun Chan Kim; Jaehwan Kim (Journal of Natural Fibers, 2020)
The purpose of this work was the production of cellulose micro-nanofibrils from wood pulps through a combination of mechanical treatments, including a recently patented process, a so-called aqueous counter collision (ACC) method followed by ultrasound treatment. Previously to ACC process, the raw pulp materials had to be downscaled to micro-sized dimension, due to the limits of collision jets nozzle diameter. Therefore, the softwood and hardwood pulps were mechanically pre-treated with valley beater refining or dry ball milling. Optical microscopy, atomic force microscopy, X-ray diffraction, thermogravimetric analysis, and gravimetric yield were estimated, to evaluate the effect of mechanical pretreatments on the proposed integrated fibrillation process. The characterizations indicated that valley beater as mechanical pretreatment was found to be more efficient compared to ball milling, of producing cellulose micro-nanofibrils in compliance with the proposed experimental procedure.